Mass media as corporative image producers: The internal public (Communication & Society, 2002)
Individual´s perceptions organizations are –at least, partly– due to the actions of mass media. However, the way in which such influence is implemented, and the way it contributes to create or clarify interpretations on the organizational reality does not seem to be homogeneus nor definitive at all. On the contrary, media information helps to stress or –sometimes- modify a previous knowledge, a previous model of reality. It is within this previous model where we find the attributes individuals tend to associate to each organization, that is, to their corporative image. Such previous knowledge is defined by what we may call Available Organizational Knowledge. AOK is responsible for most of previous models of reality that undergo the reception of further information.